Digital orthodoxy in the post-Soviet world : the Russian Orthodox Church and Web 2.0 - Suslov, M. G. (Soviet and post-Soviet politics and society., 2016)
This volume explores the relationship between new media and religion, focusing on the digital era's impact on the Russian Orthodox Church. A believer may now enter a virtual chapel, light a candle through drag-and-drop, send an online prayer request, or worship virtual icons and relics. In recent years, however, Church leaders and public figures have become increasingly skeptical about new media. The internet, some of them argue, breaches Russia's spiritual sovereignty" and implants values and ideas alien to Russian culture. This collection examines how Orthodox ecclesiology has been influenc.